Inelastic behaviors of steel shear tab connections. (25th June 2013) - Wen, Rou; Akbas, Bulent; Sutchiewcharn, Narathip; Shen, Jay
SUMMARY Inelastic behaviors of shear tab connections commonly used in modern steel buildings are investigated in this work. Full‐scale steel shear tab connections with and without concrete slab physically tested by other researchers are closely simulated by non‐linear finite element (FE) method. Different nonlinear FE features (inelastic materials, surface‐based contacts and large geometric options) are included, and different solution strategies (Newton method and Explicit Dynamic method) are employed to balance computational effort and solution accuracy. The simulations extend our understandings on shear tab connections at micro levels, including stress distribution in the connection zone, movement of the neutral axis along the beam sections and normal stress distributions along steel shear tabs and concrete slabs. It is found that the shear tabs contribute to flexural strength of the beam‐to‐column connection and the elastic–plastic theory explains the observed behavior well only when concrete slab is not present. The composite steel shear tab connections have unsymmetrical behavior under negative and positive bending moments. The compressive concrete slabs significantly increase the flexural stiffness and strength of composite shear tab connections. It is also verified that the shear studs near steel columns play a key role for the composite connections. Copyright © 2013 John Wiley & Sons, Ltd.